Murol castle (look to the village on an old postcard) - Tangopaso (Wikimedia Commons)
Notice image issue de Wikimedia Commons. Titre: Murol castle (look to the village on an old postcard). Look to the village of Murol from the Murol castle (Puy-de-Dôme, France) on an old postcard.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; Château; Carte postale